Performing the sacra : priestly roles and their organisation in Roman Britain - Esposito, Alessandra (Archaeopress Roman archaeology, 2019)
'Performing the Sacra' addresses a range of cultural responses to the Roman conquest of Britain with regard to priestly roles. The approach is based on current theoretical trends focussing on dynamics of adaptation, multiculturalism, and appropriation and discarding a sharp distinction between local and Roman cults. The perspective is shifted from a centre-periphery model towards a spectrum of cultural responses. The text investigates a wide range of published and unpublished evidence to examine three main themes: a model of priesthood organisation, the embodiment of priestly authorities in a provincial environment, and how the different depositional contexts of priestly regalia contribute to our understanding of these roles.